PENERAPAN MODEL PEMBELAJARAN KOOPERATIF METODE JIGSAW PADA MATERI BILANGAN BULAT NEGATIF PADA SISWA KELAS VI SD NEGERI 085/IV KOTA JAMBI - HERIANTO HERIANTO (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2022)
This study aims to increase motivation and learning outcomes of elementary school students at SD Negeri 85/IV Jambi City through the Jigsaw method of cooperative learning. The research design used is classroom action research. The research design setting was carried out in Class VI (six) State Elementary School 85 Jambi City in the Mathematics subject with negative integers. The subjects of the study were sixth grade teachers and sixth grade students at SDN 85 Jambi City in the 2021/2022 academic year with a total of 30 students. Data collection techniques using observation and documentation. The data analysis technique used qualitative analysis techniques and descriptive analysis. The instrument used to collect research data consisted of tests and observation sheets. Research data were analyzed descriptively by using percentages to see the trends that occur in learning activities. The research procedure was carried out cyclically. Each cycle consists of planning activities, implementing actions, observing, and reflecting activities. Based on the class actions in the first, second and third rounds, it was shown that the Jigsaw method in learning could increase student activity and learning outcomes on negative integers in 6th grade students of State Elementary School 85 Jambi City. The results of observations and tests on the learning process carried out obtained information that students' readiness to receive lessons, activeness and learning outcomes that the Reflection of Cycle I observations in the field of students showed interest in learning Students' readiness to receive lessons was 65%; active students as much as 65% and the average learning outcomes of 70.3. The action performed by the method is still used. In reflection II, the students' observations in the field showed interest in learning. Students' readiness to receive lessons was 80%; active students as much as 90% and the average learning outcomes of 72.3. The action performed by the method is still used. In Reflection III, observations in the field showed students' interest in learning. Students' readiness to receive lessons was 100%; active students as much as 100% and the average learning outcomes of 80. The actions taken by the method are still used. ABSTRAKPenelitian ini bertujuan untuk meningkatkan motivasi dan hasil belajar siswa Sekolah Dasar SD Negeri 85/IV Kota Jambi melalui model pembelajaran Kooperatif metode Jigsaw. Desain penelitian yang digunakan adalah penelitian tindakan kelas. Setting desain penelitian dilaksanakan di Kelas VI (enam) Sekolah Dasar Negeri 85 Kota Jambi pada mata pelajaran Matematika materi bilangan bulat negatif. Subyek penelitian adalah guru kelas VI dan siswa kelas VI SDN 85 Kota Jambi Tahun Pelajaran 2021/2022 dengan jumlah siswa sebanyak 30 orang. Teknik pengumpulan data menggunakan observasi dan dokumentasi. Teknik analisis data menggunakan teknik analisis kualitatif dan analisis deskriptif. Instrumen yang digunakan untuk mengumpulkan data penelitian terdiri dari tes dan lembar observasi. Data penelitian dianalisis secara deskriptif dengan menggunakan persentase untuk melihat kecenderungan yang terjadi dalam kegiatan pembelajaran. Prosedur penelitian dilakukan secara bersiklus. Pada setiap siklusnya terdiri dari kegiatan-kegiatan perencanaan, pelaksanaan tindakan, pengamatan, dan kegiatan refleksi. Berdasarkan tindakan kelas pada putaran kesatu, kedua dan ketiga menunjukkan bahwa metode Jigsaw dalam pembelajaran dapat meningkatkan keaktifan dan hasil belajar siswa pada materi bilangan bulat negatif pada siswa kelas 6 Sekolah Dasar Negeri 85 Kota Jambi. Hasil observasi dan tes pada proses pembelajaran yang dilakukan diperoleh informasi bahwa kesiapan siswa menerima pelajaran, keaktifan dan hasil belajar bahwa Refleksi Siklus I pengamatan di lapangan siswa menunjukkan minat belajar Kesiapan siswa menerima pelajaran sebanyak 65%; siswa aktif sebanyak 65 % dan hasil belajar rata-rata sebesar 70,3. Tindakan yang dilakukan metode tetap digunakan. Pada refleksi II pengamatan di lapangan siswa menunjukkan minat belajar Kesiapan siswa menerima pelajaran sebanyak 80 %; siswa aktif sebanyak 90 % dan hasil belajar rata-rata sebesar 72,3. Tindakan yang dilakukan metode tetap digunakan. Pada Refleksi III pengamatan di lapangan siswa menunjukkan minat belajar Kesiapan siswa menerima pelajaran sebanyak 100 %; siswa aktif sebanyak 100 % dan hasil belajar rata-rata sebesar 80. Tindakan yang dilakukan metode tetap digunakan.